2014
DOI: 10.1007/s00127-014-0893-1
|View full text |Cite
|
Sign up to set email alerts
|

A controlled evaluation of a targeted early case detection intervention for reducing delay in treatment of first episode psychosis

Abstract: The intervention failed to reduce R-DUP for patients making contact with or referred from community services and most patients still used hospital resources to enter treatment at the EI service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
2
33
1
Order By: Relevance
“…In addition, campaigns directed at the community or even primary care for improving mental health literacy for individual disorders, usually with the objective of reducing delay in help seeking and treatment, have generally exposed the inadequacies of such diagnosis specific strategies [11,12]. It appears that such literacy and knowledge transfer may be better applied for recognition and early intervention of a broader spectrum of mental health problems.…”
Section: Early Intervention In Psychosis and Youth Mental Health Servmentioning
confidence: 99%
“…In addition, campaigns directed at the community or even primary care for improving mental health literacy for individual disorders, usually with the objective of reducing delay in help seeking and treatment, have generally exposed the inadequacies of such diagnosis specific strategies [11,12]. It appears that such literacy and knowledge transfer may be better applied for recognition and early intervention of a broader spectrum of mental health problems.…”
Section: Early Intervention In Psychosis and Youth Mental Health Servmentioning
confidence: 99%
“…We have previously reported that this TCI led to an increase in the number of eligible FEP cases referred (Malla et al, 2014). We have previously reported that this TCI led to an increase in the number of eligible FEP cases referred (Malla et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…TCIs for early psychosis have typically focused on either the FEP or CHR stage (Addington, McGregor, Marulanda, & Raedler, 2013;Dixon, Goldman, Srihari, & Kane, 2018;Joa et al, 2007;Lloyd-Evans et al, 2011;Malla et al, 2014;Mitter, Nah, Bong, Lee, & Chong, 2014;Perez et al, 2015;Power et al, 2007;Srihari et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As studies have shown, the first point of contact for individuals with onset of psychosis is often a family physician or hospital emergency provider,30 efforts have been made to provide education to healthcare providers to facilitate appropriate referrals to specialized services. Although some research has shown that targeted educational campaigns have potential to reduce delays in the receipt of care,17 other studies have found that similar educational interventions do not result in a significant reduction in delay of referral to specialized care – even when an external specialized first-episode care program is readily available 70. Of note, one study found that if the first treatment contact point for an individual with FEP is in the community mental health setting, the delay in the receipt of specialized intervention services was even longer than for those who presented initially to emergency or crisis services 21.…”
Section: Multilevel Factors Influencing Access To Specialized Carementioning
confidence: 99%